Bacteria-assisted biogreen synthesis of radical scavenging exopolysaccharide–iron complexes: an oral nano-sized nutritional supplement with high in vivo compatibility. Issue 34 (31st July 2019) - Niknezhad, Seyyed Vahid; Najafpour Darzi, Ghasem; Kianpour, Sedigheh; Jafarzadeh, Sina; Mohammadi, Hamidreza; Ghasemi, Younes; Heidari, Reza; Shahbazi, Mohammad-Ali
Abstract : Microbial exopolysaccharides have recently served as an efficient substrate for the production of biocompatible metal nanoparticles given their favorable stabilizing and reducing properties given their favorable stabilizing and reducing properties. Abstract : Microbial exopolysaccharides (EPSs) have recently served as an efficient substrate for the production of biocompatible metal nanoparticles (NPs) given their favorable stabilizing and reducing properties due to the presence of polyanionic functional groups in their structure. In the present work, Pantoea sp. BCCS 001 GH was used to produce EPS-stabilized biogenic Fe NPs as a complex through a novel biosynthesis reaction. Physicochemical characterization of the EPS–Fe complex was performed, indicating high thermal stability, desirable magnetic properties due to the uniform distribution of the Fe NPs with the average size of ∼10 nm and spherical shape within the EPS matrix. In addition, the in vivo toxicity of the EPS-stabilized Fe NPs was evaluated to investigate their potential for the treatment of iron deficiency anemia. Biological blood parameters and organ histology studies confirmed very high safety of the biosynthesized composite, making EPS–Fe a suitable candidate with an economical and environment friendly synthesis method for a wide spectrum of potential fields in medicine.